New combinations in the fern genus Leptochilus (Polypodiaceae) - Zhang, Liang; Guo, Lei; Zhang, Li-Bing (Phytotaxa, 2018)
Following the results of a molecular phylogeny we made nine new combinations in Leptochilus based on morphological, ecological, and distributional evidence. The new combinations include: Leptochilus chilangensis, L. chingii, L. dissimilialatus, L. evrardii, L. flexilobus, L. fluviatilis, L. pentaphyllus, L. poilanei, and L. saxicola.